Investigate the role of emotional persuasion on self-efficacy and entrepreneurial attitude of sports students (an experimental study) - Elham Khoshbakht Ahmadi; Seyed Morteza Azimzadeh; Zahra Aminiroshan (Islamic Azad university, Isfahan Branch, 2022)
Objective: The aim of this study was to investigating the role of emotional persuasion on self-efficacy and entrepreneurial attitude of sports students (an experimental study).Methodology: The present study is a quasi-experimental and applied research that was conducted in two stages: pre-test and post-test. The research population consists of graduate and undergraduate students of sports sciences of Mashhad universities who according to the research protocol, 150 people were randomly selected as a sample. For data collection, the samples (150 people) were first classified into three virtual groups (telegram): positive, negative persuasion and control. An online questionnaire was provided to the samples during the pre-test and post-test. Positive and negative persuasion messages were then sent to the groups for one month.Results: The findings show that positive emotional motivation has a positive and significant effect on self-efficacy and change in attitudes toward entrepreneurship of sports students. Also, negative emotional persuasion had no effect on students' entrepreneurial attitude, but in relation to the self-efficacy variable, it shows a significant effect.Conclusion: If a person is encouraged towards entrepreneurship by various factors, we can hope that his belief and self-efficacy will be strengthened and his attitude towards entrepreneurship will change in a positive direction. Because as the results of research show, a person's emotions can be effective in this direction. Therefore, it is suggested that in order to deal with the fear and the phenomenon of student unemployment, positive incentives be used in the educational environment to see the adjustment of unemployment of this segment of society in the future